Real-world efficacy and safety of apremilast monotherapy in the management of moderate-to-severe Psoriasis - Bela J Shah; Deval Mistry; Navin Chaudhary; Shikha Shah (Wolters Kluwer Medknow Publications, 2020)
Introduction: Apremilast is the new oral drug in the management of moderate-to-severe plaque psoriasis with well-established effectiveness and safety in long-term clinical trials and a few real-world studies. However, its effectiveness and safety in Indian setup have not been reported yet. Materials and Methods: This was retrospective, single-center, longitudinal, observational cohort study where the total study period was 24 weeks. Effectiveness parameters were the proportion of patients achieving psoriasis area and severity index (PASI) 50, 75, 90, and 100 response at week 16 and 24. Safety was measured as the proportion of patients reporting ≥1 adverse event (AE) during the study period. Results: Data of a total of 70 patients were included in our study. At week 16, 76.92%, 41.53%, 15.38%, and 6.15% patients achieved PASI 50, 75, 90, and 100, respectively. At week 24, 81.53%, 58.46%, 29.23%, and 10.76% patients achieved PASI 50, 75, 90, and 100, respectively. Mean percentage reduction in PASI was 67% at week 24 and DLQI score was reduced significantly to 3.4 from mean baseline DLQI score of 10.8 (P < 0.001). 40% of patients reported ≥1 AE during the study period. 5 out of 70 patients discontinued apremilast due to AE. Nausea was most common AE reported by 21.4% patients followed by diarrhea (18.57%), headache (17.4%), vomiting (8%), weight loss (7.69%), myalgia (6.15%), and gastritis (6.15%). Most of the AEs were of mild-to-moderate severity. Conclusion: The results of this study support the long-term use of apremilast monotherapy as an efficacious and safe treatment option for the management of moderate-to-severe plaque psoriasis.